Effect of calcium hydroxide dressing on push-out bond strength of endodontic sealers to root canal dentin - Guiotti, Flávia Angélica [UNESP]; Kuga, Milton Carlos [UNESP]; Duarte, Marco Antonio Hungaro; Sant'anna Júnior, Arnaldo; Faria, Gisele [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2014)
The aim of the present study was to evaluate the effect of calcium hydroxide dressing on the bond strength of three commercially available endodontic sealers (MTA Fillapex, Sealapex, and AH Plus) to root canal dentin. Sixty slices of extracted human canines were obtained from cervical, middle, and apical root thirds. Root canals were standardized and specimens were filled and divided into six groups (n = 10): G1, MTA Fillapex; G2, Sealapex; and G3, AH Plus, with prior application of calcium hydroxide dressing; and G4, G5 and G6, without prior application of intracanal dressing. After 7 days, specimens were submitted to a push-out test. The data obtained were analyzed using the ANOVA and Tukey tests (a = 5%). Fracture modes were classified as adhesive, cohesive or mixed. The results of sealer bond strength to root canal dentin varied according to the sealer, root third and prior dressing application. Overall, calcium hydroxide dressing reduced bond strength in all root thirds, but the reduction was significant only for AH Plus, at the cervical (3.25 ± 1.69) and apical (4.43 ± 1.65) thirds (p < 0.05). AH Plus showed the highest bond strength for all root thirds (p < 0.05) compared to the other groups. G1, G2, G4 and G5 showed similar bond strength values for all root thirds (p > 0.05). In conclusion, the calcium hydroxide dressing only had a negative effect on the bond strength of AH Plus, at the cervical and apical thirds. On the other hand, the bond strength values for MTA Fillapex and Sealapex were lower than those for AH Plus and, whereas the mixed failure mode predominated for AH Plus, the adhesive failure mode predominated for MTA Fillapex and Sealapex.
Keywords: Endodontics; Calcium Hydroxide; Dentin